2013
DOI: 10.5430/wje.v3n3p40
|View full text |Cite
|
Sign up to set email alerts
|

Using High School Football to Promote Life Skills and Student Engagement: Perspectives from Canadian Coaches and Students

Abstract: In Canada, adolescent boys have been shown to have a higher high school dropout rate compared to girls. This situation is particularly evident in the country's second largest province by population, Quebec. The sport of Canadian football has recently gained in popularity in Quebec as many people believe that the sport can be used to promote both life skills and student engagement. The present study's purpose was to document coaches' and students' perspectives on student development through participation in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
0
13
0
2
Order By: Relevance
“…Past research supports these findings as a number of studies within sport have shown that participation can lead to the development of a number of positive values (Camiré & Trudel, 2010;Forneris, Camiré & Trudel, 2012;Holt, 2008). In addition, past research has shown that participation in extracurricular involvement, including those that have only focused on sport, has been linked to greater school engagement (Broh, 2002;Brown & Evans, 2002;Camiré & Trudel, 2013;Eccles & Barber, 1999;Fredricks & Eccles, 2005;Mahoney et al, 2005;Peck et al, 2008;Perry-Burney & Takyi, 2002). Given the findings regarding sport specifically and the fact that sport is the most popular extracurricular activity future research to understand how the context of sport may be unique for increasing a commitment to learn and developing social competencies is warranted.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Past research supports these findings as a number of studies within sport have shown that participation can lead to the development of a number of positive values (Camiré & Trudel, 2010;Forneris, Camiré & Trudel, 2012;Holt, 2008). In addition, past research has shown that participation in extracurricular involvement, including those that have only focused on sport, has been linked to greater school engagement (Broh, 2002;Brown & Evans, 2002;Camiré & Trudel, 2013;Eccles & Barber, 1999;Fredricks & Eccles, 2005;Mahoney et al, 2005;Peck et al, 2008;Perry-Burney & Takyi, 2002). Given the findings regarding sport specifically and the fact that sport is the most popular extracurricular activity future research to understand how the context of sport may be unique for increasing a commitment to learn and developing social competencies is warranted.…”
Section: Discussionmentioning
confidence: 74%
“…From a practical standpoint, given that gender differences in the current study are consistent with past research, it is important that practitioners work to decrease these gaps. Therefore, it is recommended that teachers, coaches, and community youth workers develop strategies to help male youth increase their academic motivation and actively engage in learning activities For example, in the last 10 years the province of Quebec has increased the number of football teams to help keep male youth motivated in school as historically Quebec has had the highest provincial dropout rate for males in the country (Camiré & Trudel, 2013). One suggestion would be to further encourage greater school engagement through the various extracurricular activities in which they participate.…”
Section: Discussionmentioning
confidence: 98%
“…Effective youth sport coaches promote a masteryorientated climate, foster fun and play, encourage social interactions, and promote positive growth opportunities (Côté & Gilbert, 2009). Moreover, youth sport coaches also act as mentors, role models, friends, and community leaders who promote the personal development of their participants (Camiré & Trudel, 2013;Falcão, Bloom, & Gilbert, 2012;Schwebel, Smith, & Smoll, 2016;Stein, Bloom, & Sabiston, 2012). Studies investigating youth development through sport found coaches' behaviours positively influenced participants' outcomes (Gould & Carson, 2008;Smith, Smoll, & Cumming, 2009).…”
mentioning
confidence: 99%
“…Studies investigating youth development through sport found coaches' behaviours positively influenced participants' outcomes (Gould & Carson, 2008;Smith, Smoll, & Cumming, 2009). More specifically, Camiré and Trudel (2013) interviewed 18 high school football players and nine of their coaches, and found those coaches' efforts to teach life-skills through sport fostered leadership and engagement inside and outside of the sport setting. Similarly, White and Bennie (2015) interviewed 22 youth gymnasts and seven of their coaches, and found positive interpersonal relationships and effective coach behaviours helped athletes cope with ISCJ Vol.…”
mentioning
confidence: 99%
“…Além de desenvolver o conteúdo esportivo, praticar esporte pode oportunizar ao aluno, uma aprendizagem significativa que lhe permita construir valores, possíveis de serem assimilados e transferidos a outros contextos de sua vida (Camiré, Trudel, 2013, Camiré, Trudel, Forneris, 2014.…”
Section: Conclusõesunclassified